The short-term effect of COVID-19 on schoolchildren's generosity - Hubert János Kiss; Tamás Keller (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We conduct two waves (W1 and W2) of an unincentivized online survey to measure the change in altruism of primary school students (N=983) toward classmates and schoolmates during the school closures due to COVID-19. The W1 responses arrived, on average, after 39 days of online education, while W2 responses arrived, on average, 31 days after W1. There is a small, but insignificant decline in generosity both towards classmates and schoolmates between waves. Students with better cognitive abilities are less likely to become selfish toward schoolmates.
Keywords: C99; D91; I24; 330; altruism; children; generosity; social preferences